Number of Sexual Partners and Sexual Activity Effect on Incidence of Syphilis in Women Sex Workers Commercial in Medan City - Riska Aulia; Rahayu Lubis; Asfriyati Asfriyati (RIRAI Publisher, 2023)
Syphilis is an infectious disease caused by treponema pallidum. Syphilis is still a health problem in the world and even syphilis is still a major cause of perinatal morbidity and mortality in many countries. Syphilis infects around 12 million people worldwide every year. The prevalence of syphilis in the female population of sex workers (WPS) infected with HIV is 16.7 percent while in WPS that is not infected with HIV 9.47 percent. The purpose of this study was to analyze the effect of the number of sexual partners and sexual activity on the events of syphilis in WPS in Medan. This research design case control with a total sample of 76 consists of 38 cases and 38 controls. The results showed that there was the influence of the number of sexual partners (p <0.001) and sexual activity (p <0.003) on the events of syphilis in WPS. In the number of sexual partners with the value of OR = 17.077 means that WPS suffering from syphilis has 17.077 times it is likely to have more than four customers per week compared to WPS who do not suffer from syphilis. Whereas in sexual activity, the value of OR = 4,429 means that WPS suffering from syphilis 4.429 times the possibility of using sexual activity more than or equal to two categories compared to WPS that does not suffer from syphilis. Suggestions This study to the Indonesian Family Planning Association (PKBI) is expected to carry out health education about the use of condoms and loyal to one partner to WPS and sex customers so that syphilis transmission does not increase.